Modeling of orthodontic treatment against periodontitis - Samoilenko, A.; Drok, V. (Actual Dentistry, 2018)
The high prevalence of major dental diseases dictates the need to find optimal means, methods of prevention and treatment taking into account pathogenetic mechanisms of development. Therefore, the study of the structure of dental and associated somatic diseases, the establishment of dominant pathogenetic factors in dental diseases in patients with general-somatic pathology, which determine the choice of adequate therapeutic and prophylactic action, is relevant. Objektiv. To develop an experimental model of periodontitis with lesions of periodontal connective tissue for experimental study of pathogenesis of periodontitis and development of methods of prophylaxis and drug treatment of this disease. Methods. The experiment was conducted on 90 White Rat lines of the Vistar line, 3 months old, which were divided into 3 groups. At the stage of pre-morphological studies, indirect signs of periodontal disease were evaluated: behavioral changes in relation to eating; study of changes in the weight of rats; study of psychomotor activity. Subsequently, the animals were examined and assessed the condition of the parodont tissues according to the following criteria: teeth movement; the presence of inflammation of the gingival margin; tooth erosion. Results. Observed changes in the weight of experimental animals. The average weight of rats before the experiment in the first group was an average of 269.5±0.2 g, after the experiment, the weight of animals decreased to 241.2±0.36 g. In the second group – to the experiment, the average weight was 270.0±0,32 g, after experiment – 230.64±0.83 g. The average weight of the rats of the comparison group almost did not change and amounted to an average of 269.5±0.19 g, and after the experiment – 271.1±0.15 g. In the rats of the first group, after the experiment, the depth of the gut pocket averaged 1.23±0.18 mm, the second group was 1.37±0.08 mm; in the group, the comparison of pathological changes in the periodontal tissues did not occur. The experimental model of periodontitis of rats made it possible to state that the osteoporotic changes of the bone of the alveolar retroperitoneum of experimental animals at the level of the incisors were accompanied by fallopian-destructive changes of the periodontal complex, edema of the gingival margin, hyperemia, sluggish exudation and movement of teeth I, II and III degrees of severity, uneven erasing teeth. In the morphological study, in the bone of the alveolar processes of rats, the destruction of bone tissue by the type of smooth and osteoclastic resorption, and also necrotic changes in the epithelial attachment cells, was observed somewhere. Conclusions. The method of modeling periodontitis using kuprenil, hydrocortisone, modeling of orthodontic treatment allowed to shorten the duration of the experiment to 21 days and get a more aggressive form of periodontitis. Key words: experimental modeling, rats, periodontitis.